(untitled) (Docentes 2.0 Journal, 2025)
Constant technological, scientific, and cultural evolution requires professionals to continually update and strengthen their skills, especially in education. The research objective was to identify and analyze the main findings and trends on the most effective pedagogical support strategies to improve teaching practices in basic education. The research was based on the systematic method, positivist paradigm, quantitative approach, topic narrative design, exploratory and cross-sectional documentary type. The search was carried out systematically using the Prisma method, with searches in repositories such as Scielo, Scopus, Web of Science, and Google Scholar. The terminologies used in the exploration were support, pedagogical support, teacher, and basic education. As a result, 197 research titles were obtained, of which 16 were selected that met the inclusion criteria. The findings indicate that pedagogical support is essential to strengthening teachers’ teaching practices, and implementing more systematic and personalized programs adapted to the specific needs of each educational context is suggested.